Երեք նվիրում Ղազարոս Սարյանին - Արթուրի Յոլչյան Էլեն (Musical Armenia, 2010)
Descriptive - analytical article of a student of 1st course of Musicological department of YSC called “Three offerings to Lazar Saryan” - an appeal to the works of three authors: “Prelude” N 3 E. S. Hovhhanisyan (1960), and students of Lazar Martirosovich - “Piano Sonata “ of T. E. Mansuryan and” Quartet “N 1 of V. A. Adzhemyan. It is a sign of respect and love, expressed in the writings of different hands, a kind of musical thinking and writing style. Essay written by V. A. Adzhemyan after the death of his favorite teacher, 4 months later.